Addressing Diversity and Difference in Contemporary Spanish Lesbian Literature: Reading Illy Nes’s El lago rosa and Cristina Cuesta’s “Zoe y Haydee” - Megan Sheldon (Studies in 20th & 21st Century Literature, 2018)
Illy Nes’s novel El lago rosa (The Pink Lake, 2004) and Cristina Cuesta’s short story “Zoe y Haydee” (Zoe and Haydee, 2007) depict travel and cross-cultural queer relationships that call attention to racial and class differences as well as ethnic and cultural divides. Both narratives raise questions concerning the representation of queer women of color in Spanish fiction of the new millennium. This article focuses on the diverse cultural, political and personal struggles that surround the formation and negotiation of sexual identity, emphasizing the fact that LGBTQ identity is not necessarily cross-culturally or universally constructed around identical interests, desires, or experiences.
Keywords: Spanish Literature; LGBTQ; Sexuality; Gender